Ainbo : spirit of the Amazon [videorecording (DVD)] - Zelada, José; Claus, Richard; Cleveland, Brian; Cleveland, Jason, 1979-; Wilson, Larry, 1948- (Shout! Factory, 2022)
Ainbo was born and grew up in the deepest jungle of the Amazon. One day she discovers that her homeland is being threatened. With the help of her spirit guides "Dillo," a cute and humorous armadillo, and "Vaca" a heavy-set tapir, Ainbo embarks on a journey to save her homeland. As she fights to save her paradise against the greed and exploitation by illegal miners, she struggles to reverse this destruction and the impending evil of the "Yacaruna", the darkness that lives in the Amazon. Guided by her mother's spirit, Ainbo is determined to save her land before it's too late.